Public attitudes toward COVID-19 prevention and control in China - Zhu, Wei (Frontiers in Public Health, 2024)
Based on the data of the Chinese General Social Survey (CGSS) in 2021, this study aims to investigate the public attitudes toward COVID-19 prevention and control in China. The household survey CGSS 2021 contains 8,148 valid samples gathered from 320 communities across 19 provinces in China. The logistic regression model is adopted to examine the relationship between public attitudes and influencing factors. The results show that the vast majority of respondents firmly believe that the government has the authority to implement strict measures; their confidence in the government and in the healthcare system has increased; and they willingly choose to be vaccinated. The regression results suggest that gender, age, health condition, political affiliation, source of information, sense of fairness, socio-economic status, and place of residence are significantly associated with individuals’ attitudes toward COVID-19 prevention and control. These findings highlight the importance for the government to design epidemic or pandemic policies based on data and to tailor them toward specific demographics.